Summary: Egilio saga / Egil’s Saga (Scandinavistica Vilnensis, 2012)
This is a second, revised and annotated edition of the translation of Egil’s Saga into Lithuanian. It is supplied with introductory essays by Svetlana Steponavičienė and Ugnius Mikučionis, the translator’s commentary to the text, the index of proper names and maps. The verses in the saga have been translated by Leonas Petravičius, except for the skaldic poem “Sonatorrek”, which has been translated by Rasa Ruseckienė.